Consumer Buying Decision for Smartphones: An Analysis of Price, Brand, and Features - Manandhar, Raju Bhai; Timilsina, Jagat (Journal of Nepalese Business Studies, 2023)
In today's digital age, smartphones have become indispensable tools, serving as the primary means of communication, text messaging, email correspondence, web browsing, file storage, audio recording, and photography. The study aimed to examine the effect of price, brand, and product features on smartphone consumer buying decisions. The research employed a descriptive and causal-comparative research design. The study targeted individuals living in the Kathmandu Valley with prior smartphone experience. Three hundred forty respondents were selected using a convenience sampling technique. Data collection was executed through a five-point Likert scale questionnaire. The study mainly adopted correlation and regression to analyze the data. The study's findings revealed that price, brand, and product features had positive associations with consumer purchasing decisions toward smartphones. Interestingly, brand and product features significantly influenced consumer purchasing decisions, whereas price had no significant influence. Gender affects consumer buying decisions and product features, but not price and brand. As per the result, product features are essential in ensuring customer buying decisions, while brands create value for smartphones. Therefore, companies must maintain the brand image and adjust the latest product features to meet consumer expectations. The study has considered only three explanatory variables, i.e., price, brand, and product features, so future researchers can test the impact of other independent variables on the purchase decisions of smartphone consumers in a large sample size.